Increasing levels of pretreatment HIV drug resistance and safety concerns for dolutegravir use in women of reproductive age. (1st September 2019) - Inzaule, Seth Chekata; Jordan, Michael R.; Cournil, Amandine; Vitoria, Marco; Ravasi, Giovanni; Cham, Fatim; Le, Linh-Vi; Dzangare, Janet; Hamunime, Ndapewa; Mutenda, Nicholus; Aghokeng, Avelin; Bissek, Annez; et al.
Abstract : N/A: Use of dolutegravir-based first-line antiretroviral therapy (ART) in response to rising levels of pretreatment HIV drug resistance (PDR) to non-nucleoside reverse transcriptase inhibitors (NNRTIs) may be limited, given safety concerns for birth defects in women of child-bearing potential. Pooled data from 11 nationally representative surveys show that NNRTI PDR in women is nearly twice that in men, exceeding 10% in 8 of 11 countries monitored, suggesting the urgent need for a non-NNRTI-based ART regimen in this population.